2019
DOI: 10.1021/acs.iecr.9b00520
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Coupled Process for Catalytic Cracking of High-Acid Crude Oil

Abstract: To process high-acid crude oil by catalytic cracking technology, a coupled process (FCD–FCC) involving fluid catalytic deacidification (FCD) of high-acid crude oil over a spent catalyst and fluid catalytic cracking (FCC) of heavy oil over a regenerated catalyst was proposed. Experiments were carried out in a confined fluidized bed reactor to test the feasibility of this process. The results indicate that the spent catalyst can be used for deacidification of high-acid crude oil to restrain the overcracking of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The quality of crude oil resources worldwide is deteriorating [1,2]. After 2020, heavy crude oil reserves are expected to account for almost half of all recoverable reserves [3].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of crude oil resources worldwide is deteriorating [1,2]. After 2020, heavy crude oil reserves are expected to account for almost half of all recoverable reserves [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in 1942, fluid catalytic cracking (FCC) has become the main driver for oil refining performance improvement. , Over the years, it was found that FCC is a versatile process that can convert feeds of different originsvacuum oils, residual oils, crude oil, scrap tires pyrolysis oil, polyethylene plastic waste, biomass derived oilsinto high value transportation fuels and light olefin feeds for the petrochemical industry. Among all independent variables which affect the FCC unit (FCCU) performance, the feedstock quality has the biggest impact. While the processing of straight run vacuum gas oils (SRVGOs) in the FCCU is much more straightforward, the processing of secondary gas oils (from coker, visbreaker, and residue hydrocracker) is more challenging . Secondary gas oils are indeed characterized by a higher basic nitrogen content and by a higher level of refractory condensed aromatic compounds. The performance of the FCCU is therefore strictly correlated to the amount and the quality of the secondary gas oil fraction present in the FCC feed blend. , …”
Section: Introductionmentioning
confidence: 99%
“…Crude oil resources around the world are facing heavy quality challenges. , It is estimated that the reserves of heavy crude oil will account for about 50% of the global recoverable reserves after 2020 . Fluid catalytic cracking (FCC) exerts a significant effect on the conversion of heavy oil into light fraction products, such as dry gas, liquefied petroleum gas (LPG), high octane number (HON), and gasoline and light cycle oil (LCO) in refineries .…”
Section: Introductionmentioning
confidence: 99%